Femmes orientales et photographes commerciaux. La construction d’un imaginaire dans la production photographique des années 1860-1880 - Lionel Gauthier (Cybergeo)
This paper analyses the construction of the image of oriental women in the production of commercial photography between the 1860’s and the 1880’s. It is based on an unpublished corpus: a collection of 1568 photographs purchased by the Genevan traveler Alfred Bertrand (1856-1924) between 1874 and 1883. By studying this corpus, this paper shows the differential photographic treatment existing between oriental women and oriental men. It first details the techniques used by the photographers yielding this differentiation, such as the process of decontextualization and recontextualization and the association between eroticization and typification. It then suggests some possible explanations for these differences, such as the constraints imposed on the photographers (norms of the societies of origin of the photographers, rules of the societies photographed, material conditions), and the imaginaries and ideologies of these photographers (fascination with oriental women, the supposed inferiority of oriental societies). Finally, it highlights the role of the customers of these photographers.